Prevalence of Anemia Among Women of Reproductive Age in Rural Haryana, India. (7th June 2021) - Yeung, Lorraine; Duggal, Mona; Das, Reena; Rosenthal, Jorge; Bhardwaj, Swati; Kankaria, Ankita; Kaur, Manmeet; Senee, Hari; Kumar, Akash; Rose, Charles; Dhanjal, Gursharan Singh; Kumar, Vishal; et al.
Abstract: Objectives: Anemia is a public health problem in women of reproductive age in many low- and medium-income countries including India. Maternal anemia can cause low birth weight, impaired fetal growth, and preterm birth. We assessed the baseline prevalence of anemia, iron deficiency (ID), iron deficiency anemia (IDA), and inflammation using c-reactive protein (CRP) among non-pregnant, non-lactating women of reproductive age living in the Ambala District, Haryana, India prior to the start of a wheat flour fortification program. Methods: We conducted a multistage cluster probability household and biomarker survey and analyzed venous blood samples from non-pregnant, non-lactating women aged 18–49 years residing in rural areas of two subdistricts in the Ambala District. Factors of interest were: anemia, hemoglobin < 12.0 g/dL; ID, serum ferritin < 15μg/L;  IDA,  presence of both anemia and iron deficiency; inflammation, CRP > 5 mg/L. We used the BRINDA regression adjustment for ferritin to account for inflammation. Prevalence and 95% confidence intervals (CI) for anemia, ID, IDA, and CRP were estimated. Results: Among 775 non-pregnant, non-lactating women of reproductive age, 54.3% (95% CI; 50.7, 58.0) had anemia, 86.9% (95% CI; 84.3, 89.2) were iron deficient, and 15.1% (95% CI; 12.5, 18.1) had inflammation. Among those with anemia, 58.2% (95 CI; 54.3, 62.0) had iron deficiency anemia. Conclusions: Anemia, iron deficiency, and iron deficiency anemia among non-pregnant, non-lactating women of reproductive age in Haryana are significant public health concerns. The findings from the survey helped quantify the burden of inadequate iron intake and informed the Haryana government's prevention strategy aimed at reducing micronutrient deficiencies through a wheat flour fortification program. Funding Sources: Centers for Disease Control and Prevention.